Green HRM Practices and Organizational Citizenship Behavior to Environment (OCBE): Analysis of Banking Sector in Bahrain - Habil Slade Ogalo; Seerat Fatima; Amna Hasnain (Contemporary Research in Business, Management and Economics Vol. 7, 2024)
The aim of the present study was to examine the relationship between green HRM and Organizational citizenship behavior for the environment (OCBE). Organizations that have managed to work effectively in this regard have managed to reap many benefits including enhancing their citizenship outlook in the society. The study tested the impact of green recruitment, green training and green rewards on OCBE in the banking sector of Bahrain. Organizational citizenship behaviors popularly known as OCB are one of the salient management concepts these days and have received much empirical attention over the recent past across the organizational behavior domain. The bootstrapping results on the hypothesized relationship confirmed a significant relationship between green recruitment and OCBE. Four major banks in Bahrain were selected for the present study. The banks were chosen based on initial information obtained pertaining to their implementation of Green HR practices (green recruitment, training and rewards) in the company over the past three years. Accordingly, the study also found support for green training and OCBE followed by empirical significance for green rewards and OCBE relationship simultaneously. The research findings provide clear evidence of the importance of green HRM practices in improving environmental citizenship within organizations. Notable findings from the study have implications for further research.